2010
DOI: 10.1021/mp900193e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HEPES Buffer on the Uptake and Transport of P-Glycoprotein Substrates and Large Neutral Amino Acids

Abstract: HEPES has been widely employed as an organic buffer agent in cell culture medium as well as uptake and transport experiments in vitro. However, concentrations of HEPES used in such studies vary from one laboratory to another. In this study, we investigated the effect of HEPES on the uptake and bidirectional transport of P-gp substrates employing both Caco-2 and MDCK-MDR1 cells. ATPdependent uptake of glutamic acid was also examined. ATP production was further quantified applying ATP Determination Kit. An addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…Luo et al showed that ATP production increased with 70% in MDCK-MDR-1 cells grown in culture medium with 20 mM HEPES for 6-7 days compared to the same cell line in medium without HEPES. This caused an increase in MDR-1 efflux activity, which could be a relevant effect in our model (26). Care should be taken when interpreting data from artificially buffered cell cultures, as the buffer compounds may exert an influence, independent of the buffering effect.…”
Section: The Main Effect Of the Additionally Buffered Media Was Most mentioning
confidence: 98%
See 1 more Smart Citation
“…Luo et al showed that ATP production increased with 70% in MDCK-MDR-1 cells grown in culture medium with 20 mM HEPES for 6-7 days compared to the same cell line in medium without HEPES. This caused an increase in MDR-1 efflux activity, which could be a relevant effect in our model (26). Care should be taken when interpreting data from artificially buffered cell cultures, as the buffer compounds may exert an influence, independent of the buffering effect.…”
Section: The Main Effect Of the Additionally Buffered Media Was Most mentioning
confidence: 98%
“…HEPES, MOPS, and TES have all been found to exert a wide range of different adverse effects in different cell culture systems (24)(25)(26)(27). Luo et al showed that ATP production increased with 70% in MDCK-MDR-1 cells grown in culture medium with 20 mM HEPES for 6-7 days compared to the same cell line in medium without HEPES.…”
Section: The Main Effect Of the Additionally Buffered Media Was Most mentioning
confidence: 99%
“…Digoxin is not a substrate for Bcrp [58], but other studies have indicated that the poor BBB permeability of digoxin is not explained by P-gp alone [11,38]. Verapamil has been used as a P-gp inhibitor in concentrations from 5 to 150 μM [23,[59][60][61], but it has also been shown to inhibit Mrp activity in concentrations of 5-10 μM [45,62] as well as Bcrp activity, although not in the concentration range applied here [63,64]. In our study, 50 μM verapamil lowered the efflux ratio of digoxin to 1.1, whereas the Bcrp inhibitor, Ko 143, had no effect on the digoxin transport indicating that the verapamil inhibition of A-L digoxin transport we observed was due to inhibition of P-gp or Mrp's.…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 99%
“…[32] ] of the buffer. The HEPES buffer system is extensively used for physicochemical and biological investigations; [33] therefore, all of the experiments were run in this buffer. Figure 1 shows the adsorption kinetics of DiC 8 -PC dissolved in the HEPES buffer at the interfaces with air, and with air saturated with PFH, for three selected concentrations of DiC 8 -PC.…”
Section: Adsorption Of Dic8-pc In the Presence Or Absence Of Perfluormentioning
confidence: 99%